PENERAPAN TEORI HUMANISTIK MODEL ACCELERATED LEARNING MELALUI PENDEKATAN SAVI DALAM PEMBELAJARAN PAI UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PESERTA DIDIK DI SDN DAYEUHKOLOT 03 - Kurniasih, Siti Rohmah; Tarsono, Tarsono; Azizah, Rina Nur; Maulidah, Siti Rohmah; Risydayani, Zakia Ridhatilla (Attadib: Journal of Elementary Education, 2023)
This study aims to analyze the application of the humanistic theory of accreted learning models through the somatic, auditory, visual, and intellectual (SAVI) approach in PAI learning and determine its impact on students' critical thinking skills. This study uses a qualitative descriptive method with data analysis techniques, namely conducting library research and field research, and then reducing, presenting, and verifying the data before drawing conclusions. Based on the results of the research, the application of the humanistic theory of accreted learning models through the somatic, auditory, visual, and intellectual (SAVI) approach is carried out in three stages, namely planning, implementation, and evaluation. The most typical process of applying this theory found by researchers at Darmayanti Cimaung Middle School is the existence of lesson plans that are able to assist educators in carrying out the learning process according to the learning needs of students so that they are in accordance with the expected goals, as well as the existence of socio-emotional learning at the beginning of learning by using the STOP method and reflection activities that further encourage individual self-awareness of various strengths and weaknesses during the learning process to then carry out improvements in the next lesson. In conclusion, the application of the theory of the humanistic model of accelerated learning through the somatic, auditory, visual, and intellectual (SAVI) approach in PAI learning is able to improve students' critical thinking skills, which are characterized by increased fluency, flexibility, originality, and elaboration abilities in studentsTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//   This page is in English Translate to Indonesian    AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBengaliBulgarianCatalanCroatianCzechDanishDutchEnglishEstonianFinnishFrenchGermanGreekGujaratiHaitian CreoleHebrewHindiHungarianIcelandicIndonesianItalianJapaneseKannadaKazakhKhmerKoreanKurdish (Kurmanji)LaoLatvianLithuanianMalagasyMalayMalayalamMalteseMaoriMarathiMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanSimplified ChineseSlovakSlovenianSpanishSwedishTamilTeluguThaiTraditional ChineseTurkishUkrainianUrduVietnameseWelsh Always translate English to IndonesianPRO Never translate English Never translate www.jurnalfai-uikabogor.org